Reduced concentrations of selenium in mild Crohn's disease. Issue 2 (February 1988) - Hinks, L J; Inwards, K D; Lloyd, B; Clayton, B
Abstract : The concentrations of selenium, zinc, and copper were determined in whole blood, plasma, and leucocytes in 20 patients with relatively mild Crohn's disease, nine of whom were being treated with steroids, and compared with those of a control group. There was a significant decrease in the concentration of selenium in the leucocytes as well as in whole blood and plasma in the patients. Steroids seemed to affect only the concentrations of zinc and copper in plasma. The concentrations of copper and zinc in whole blood, plasma, and leucocytes in patients not taking steroids were not significantly different from those of the control group. The observations suggest that those patients with an apparently satisfactory whole body concentration of copper and zinc may still be at risk of a decrease in the body content of selenium.